2013
DOI: 10.2478/10004-1254-64-2013-2394
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Cytological Examination of Rat Reproductive Tissue After Short-Time Intermittent Radiofrequency Exposure

Abstract: The unfavourable outcomes of mobile phone use on male fertility have still not been fully elaborated. To establish the potentially adverse effects of everyday exposure to radiofrequency radiation (RF) on humans, we performed a controlled animal study that aimed to investigate the infl uence of RF radiation on rat testis histology as well as the amount, mobility, and structure of epididymal free sperm cell population. Eighteen adult male rats were divided into two groups of nine. One group comprised sham-expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Reliable with our findings, it was reported that cell phone radiation decreased sperm parameters in humans [3,5,33] and rats [20,21]. In contrast to our results, exposure to EMF did not induce any negative effects on sperm quantity, quality, and morphology [8,51,52]. LXRs improving action on sperm quality could be attributed to its antioxidant, antinflammatory properties besides its endocrinal action.…”
Section: Discussionsupporting
confidence: 87%
“…Reliable with our findings, it was reported that cell phone radiation decreased sperm parameters in humans [3,5,33] and rats [20,21]. In contrast to our results, exposure to EMF did not induce any negative effects on sperm quantity, quality, and morphology [8,51,52]. LXRs improving action on sperm quality could be attributed to its antioxidant, antinflammatory properties besides its endocrinal action.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it is possible that the 50 Hz ELEF can affect the sperm quality parameters depend on both waveform and amplitude of the applied magnetic field. In addition, some studies demonstrated that exposure to electromagnetic fields had no adverse effects on sperm quality, viability, and morphology [28, 32]. It is probable that ELEF increased sperm viability through reduction of ROS production in sperm cells as previously stated by Gholami et al [10, 33, 34].…”
Section: Discussionmentioning
confidence: 81%
“…On the other side, the evidence from studies on male reproductive system suggest that RFR exposure might negatively affect male fertility. The increased sperm cell death rate accompanied by reduced sperm quality and motility seems to be the more recurring effects, due to RFR exposure in SD rats [38,39,40]. Guo et al, based on their findings from the most recent study conducted in SD rats suggested that the RFR-induced impaired sperm quality in SD rats might be accounted for by the increased apoptosis of testicular cells and the disruption of the secreting function of Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…An haemocytometer was used for microscopically determining the quality, quantity and structure of free sperm cells taken from the epididymis. This study revealed no statistically significant changes in any of the evaluated endpoints [39].…”
Section: Reproductive/developmental Toxicity In Vivo Investigationsmentioning
confidence: 98%